Incidencia socioeconómica de las barreras arancelarias aplicadas a las importaciones de calzado en la parroquia Quisapincha de Ambato, provincia de Tungurahua y propuesta de mejora en la producción y comercialización del producto. - Salcedo Baldeón, Ivonne Lissette (2014)
This paper provides information about the history, development and current situation of artisanal footwear sector in the parish of Quisapincha- Ambato. The problem was that there were no restrictions on footwear imports therefore the domestic footwear industry was affected, many craftsmen from this parish migrated to other cities and as a result the number of producers declined markedly. The current government implemented measures to reactivate the footwear industry because many of the manufacturers and artisans who formed the production chain had to face a major crisis by the indiscriminate introduction of footwear from China, Colombia, and Brazil. The beneficiaries of this improvement proposal in the production and marketing of the product will be the craftsmen of Quisapincha who should work together with the Chamber of footwear of Tungurahua (CALTU) which is focused on providing technical assistance to various footwear producers who are trained in a continuous basis. The study aims to present an improvement proposal for footwear production and marketing; The study will focus in knowing the likes and preferences of the market through surveys to 400 customers that visit the leather and footwear fair of Quisapincha which is organized every weekend. The Study will also reveal through field visits, the socioeconomic influence of this manufacturing sector in the past six years.